Gene functions in adult cuticle pigmentation of the yellow mealworm, Tenebrio molitor. (February 2020) - Mun, Seulgi; Noh, Mi Young; Kramer, Karl J.; Muthukrishnan, Subbaratnam; Arakane, Yasuyuki
Abstract: In many arthropod species including insects, the cuticle tanning pathway for both pigmentation and sclerotization begins with tyrosine and is responsible for production of both melanin- and quinoid-type pigments, some of which are major pigments for body coloration. In this study we identified and cloned cDNAs of the yellow mealworm, Tenebrio molitor, encoding seven key enzymes involved in this pathway including tyrosine hydroxylase (TmTH), DOPA decarboxylase (TmDDC), laccase 2 (TmLac2), Yellow-y (TmY-y), arylalkylamine N -acetyltransferase (TmAANAT1), aspartate 1-decarboxylase (TmADC) and N -β-alanyldopamine synthase (Tmebony). Expression profiles of these genes during development were analyzed by real-time PCR, revealing development-specific patterns of expression. Loss of function mediated by RNAi of either 1) TmTH or TmLac2, 2) TmDDC or TmY-y, and 3) TmAANAT1, TmADC or Tmebony resulted in pale/white, light yellow/brown and dark/black adult body coloration, respectively. In addition, there are three distinct layer/regional pigmentation differences in rigid types of adult cuticle, a brownish outer exocuticle (EX), a dark pigmented middle mesocuticle (ME) and a transparent inner endocuticle (EN). Decreases in pigmentation of the EX and/or ME layers were observed after RNAi of TmDDC or TmY-y . In TmADC- or Tmebony-deficient adults, a darker pigmented EX layer was observed. In TmAANAT1-deficient adults, trabeculae formed between the dorsal and ventral elytral cuticles as well as the transparent EN layer became highly pigmented. These results demonstrate that knocking down the level of gene expression of specific enzymes of this tyrosine metabolic pathway leads to abnormal pigmentation in individual layers and substructure of the rigid adult exoskeleton of T. molitor . Graphical abstract: Image 1 Highlights: CDNAs for seven key enzymes involved in Tenebrio cuticle tanning were cloned. Rigid cuticle has brownish exo-, dark meso- and transparent endocuticular layers. RNAi of target genes causes abnormal regional and temporal pigmentation. NBAD and NADA are associated with brownish exocuticle and less pigmented endocuticle. NADA-tanning produces a dark pigmented mesocuticle layer and overall adult body color.